TEORI SIBERNETIK DAN IMPLIKASINYA TERHADAP MODEL PEMBELAJARAN BRAIN BASED LEARNING PADA PEMBELAJARAN PKN - Damayanti, Siska; Suryadi, Karim (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2023)
The world of education, especially Civics learning, requires innovation and variation in the learning methods applied. The brain-based learning method is very interesting because optimizing brain work can be started in a simple way. Educators' knowledge of fundamental questions about "what is good for a child's brain?" is the essence of applying this learning method. This is research that uses a qualitative approach with a literature study method. The process of data analysis is done through reduction, display, verification, and drawing conclusions. The results of the study state that the Brain-Based Learning Method with cybernetic learning theory is an innovative alternative in Civics subjects, so that learning is more efficient and fun. This learning method can be carried out in simple ways, such as paying attention to brain nutrition in students, paying attention to brain relaxation such as stretching or relaxing and listening to music, paying attention to plants and class aromas that can improve brain performance, paying attention to recess, and playing games in class.